Magnetic structure of an antiferromagnet NdRh2Zn20 investigated by powder neutron diffraction. Issue 1 (1st March 2022) - Yamamoto, R.; Shimura, Y.; Umeo, K.; Takabatake, T.; Damay, F.; Mignot, J.-M.; Onimaru, T.
Abstract: Powder neutron diffraction measurements were carried out to investigate the magnetic structure of the antiferromagnet NdRh2 Zn20 . The magnetic reflections observed for T ≤ 1.0 K are indexed by the propagation vector of k = (1/2, 1/2, 1/2). From the analysis of the intensity of magnetic reflections, a magnetic structure described by the Γ6 representation is proposed. The magnetic moments are parallel to the [ 11 2 ¯ ] or [ 1 ¯ 10 ] direction and stacked with a sequence of up-up-down-down along the [111] direction.